Ice-Nucleating Proteins of Bacterial Origin. Report I. General Characterization and Classification - Gulevskiy, A. K.; Relina, L. I. (Problems of Cryobiology and Cryomedicine, 2010)
A general description and characteristics of proteinaceous nucleators, which were found in the bacteria of genera Pseudomonas, Erwinia, Flavobacterium and Xanthomonas, are presented in the review. The suggested classification types of bacrerial nucleators are discussed.